NÃO É APENAS UMA GRIPEZINHA: relações entre a difusão da covid-19 e as dinâmicas das interações socioespaciais no estado do Maranhão - JARDIM, Richard Oliveira (2022)
In recent years (2020-2021), the world has experienced and continues to experience the serious problem of the Covid-19 pandemic. In this way, the objective of this study was to evaluate the spread of Covid-19, as well as deaths in the 217 municipalities of the state of Maranhão, confronting variables in the dimensions of infrastructure, economic, health, and education in the period from March 2020 to March 2021 The research is based on the theories of historical materialism, analyzing the data in the quanti-qualitative method, to carry out a descriptive, but also exploratory work. To carry out the research, we used secondary data that were collected on the platform "Panel da Covid 19" of the Secretary of Health of the State of Maranhão and socioeconomic, infrastructure, and demographic data extracted either through the Maranhense Institute of Socioeconomic and Cartographic Studies ( IMESC), on the Ecological and Economic Zoning platform of the State of Maranhão, sometimes on the IBGE portal and sometimes on the Atlas of Human Development, which were specialized from choropleth maps, using the software Qgis 3.18.2, commonly known as Zürich. Initially, the work brings a global and Brazilian panorama on the spread of the virus by countries and states and later delving into the territories of Maranhão, from three scenarios: March 20 to May 30, 2020; August 21, 2020, to January 2021 and January 21, 2020, to March 20, 2020, which correspond to the first period of spread of the virus by the state, the regression in the number of cases of infection by the disease and the increase in the number of cases of infection, respectively. The results provide information on 1. The relationship between the urban hierarchy and centrality through the road network to understand the arrival and spread of the virus, identifying the entry points of the virus; 2. Intercity relations, road network, and population density as a spreader of Covid-19; and 3. Correlation between vulnerability based on the social deprivation index and contagion with Sars-coV-2.